2020
DOI: 10.1007/s00204-020-02798-z
|View full text |Cite
|
Sign up to set email alerts
|

Monocrotaline-induced liver toxicity in rat predicted by a combined in vitro physiologically based kinetic modeling approach

Abstract: The aim of the present study was to use an in vitro-in silico approach to predict the in vivo acute liver toxicity of monocrotaline and to characterize the influence of its metabolism on its relative toxic potency compared to lasiocarpine and riddelliine. In the absence of data on acute liver toxicity of monocrotaline upon oral exposure, the predicted dose-response curve for acute liver toxicity in rats and the resulting benchmark dose lower and upper confidence limits for 10% effect (BMDL 10 and BMDU 10) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
(127 reference statements)
0
13
0
Order By: Relevance
“…An observation that can be taken into account in PBK modeling by including the kinetic parameters Vmax and Km for the respective clearance in the model code. In a QIVIVE study on the monocrotaline-induced liver toxicity in rats predicted by a PBK modeling-facilitated reverse dosimetry, the role of the OCT1 transporter was taken into account, providing a proof of principle on how to deal with differences in PA absorption [43].…”
Section: Adme Characteristics As Key Determinants In Pa Toxicitymentioning
confidence: 99%
“…An observation that can be taken into account in PBK modeling by including the kinetic parameters Vmax and Km for the respective clearance in the model code. In a QIVIVE study on the monocrotaline-induced liver toxicity in rats predicted by a PBK modeling-facilitated reverse dosimetry, the role of the OCT1 transporter was taken into account, providing a proof of principle on how to deal with differences in PA absorption [43].…”
Section: Adme Characteristics As Key Determinants In Pa Toxicitymentioning
confidence: 99%
“…In general, most toxic PA types including retrorsine, riddelliine, senecionine, senkirkine, and lasiocarine are mainly metabolized by CYP3A4, which account for 30–50% of the hepatic CYP isoforms ( Teschke et al, 2021 ). While PAs such as monocrotaline are mainly metabolized by the CYP2A6 ( Suparmi et al, 2020 ). In the present study, because CYP3A4 is the predominant CYP isoform accounting for the RTS intoxication, we, therefore, focus on the study of the interaction between GA and CYP3A4 in our animal and cell models.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent benchmark dose (BMD) modeling can be applied on the predicted in vivo dose-response data, enabling definition of a point of departure (PoD) for risk assessment, such as a BMDL x (the lower confidence limit of the benchmark dose causing an x% effect above background level) and BMDUx (the upper confidence limit of the benchmark dose causing an x% effect above background level). PBK modelling has recently been applied to describe the kinetics of three PAs, including riddelliine, lasiocarpine and monocrotaline [20,[26][27][28][29]. ▶ Fig.…”
Section: Physiologically-based Kinetic (Pbk) Modellingmentioning
confidence: 99%
“…For the parent PAs, in vitro studies using either microsomal incubations or rat hepatocyte sandwich cultures have revealed substantial variation in metabolic clearance between the examined PAs [20][21][22]. Based on kinetic data from in vitro liver microsomal incubations, clearance of lasiocarpine was shown to be about 10-fold more effective than that of riddelliine and 43-fold more effective than that of monocrotaline (▶ Table 2) [22]. These results were in line with data from Lester et al, (2019) [21], who studied the clearance of PAs in rat hepatocyte sandwich cultures and reported the in vitro clearance for these three PAs to also decrease in the order: lasiocarpine > riddelliine > monocrotaline [21].…”
Section: Mwmentioning
confidence: 99%
See 1 more Smart Citation